Pengaruh Krisis Ekonomi Terhadap Sistem Perputaran Keuangan Bank Dalam Novel Negeri Para Bedebah Karya Tere Liye - Gabriela Spanic Aritonang; Wafiq Nur Kholidan; Eva Dwi Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This journal reviews the influence of the economic crisis on the bank's financial turnover system in the novel Land of the Bedebah by Tere Liye. This research aims to determine the impact of the economic crisis on the bank's financial turnover system which could even have the impact of a bank collapsing. The method used in this research is descriptive qualitative using research data sources from books and journals. The results of this research are that the economic crisis has had a significant impact on the sustainability of banks. Where with the economic crisis the entire financial system freezes, interest on bank savings automatically decreases and many customers want to withdraw all their savings, but the bank's financial circulation which gives customer savings as loans to third parties makes the bank confused about how to provide customer money. And on the other hand, it will also be difficult for banks to withdraw all the money that has been given to third parties quickly. The impact of the economic crisis, apart from causing share prices to fall, will also cause financial turnover in banks to become messy. Where debtors try to withdraw their money and on the other hand creditors cannot return their loans instantly. So with this problem, if the bank cannot overcome it and the economic crisis continues, it could result in the bank collapsing.